2013
DOI: 10.2147/ppa.s42133
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the quality of life of people with thalassemia major between 2001 and 2009

Abstract: BackgroundThe prolonged survival of patients with thalassemia major as a result of the novel therapeutic strategies introduced in the last decade makes patient quality of life an important issue. This study investigated the changes occurring in overall quality of life in patients with thalassemia in the last decade.MethodsThis was a population-based cross-sectional survey of quality of life in the entire population with thalassemia major resident in the Liguria region of Italy from 2001 to 2009. The self-admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 20 publications
2
16
3
Order By: Relevance
“… 7 , 9 This study shows that normal controls have significantly higher score than patients with β-thalassemia in physical domain; patients are subject to the long-term side effects of chronic anemia and repeated transfusions. 4 , 10 - 13 However, we have found that patients with β-thalassemia have significantly higher score in the social domain, in contrary to other studies results. 4 , 10 , 14 - 16 Other studies, however reported that their study subjects felt that the disease did not affect their family or social relationships.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“… 7 , 9 This study shows that normal controls have significantly higher score than patients with β-thalassemia in physical domain; patients are subject to the long-term side effects of chronic anemia and repeated transfusions. 4 , 10 - 13 However, we have found that patients with β-thalassemia have significantly higher score in the social domain, in contrary to other studies results. 4 , 10 , 14 - 16 Other studies, however reported that their study subjects felt that the disease did not affect their family or social relationships.…”
Section: Discussioncontrasting
confidence: 99%
“…3 Morbidity and mortality related to thalassemia have been reduced significantly with modern medical treatment, and QOL should now be considered an important index of effective health care and an essential outcome when considering options for treatment for individual patients and the allocation of health care resources. 4 As per the World Health Organization (WHO) definition, QOL is individuals’ perceptions of their position in life in the context of the culture and value systems in which they live, and in relation to their goals, expectations, standards and concerns. 5 In clinical practice the QOL assessments will assist clinicians in making judgments in regards to the areas in which a patient is most affected by disease, and in making treatment decisions.…”
mentioning
confidence: 99%
“…The patients' self-support can stimulate their forgotten abilities and apply them to eliminate the defects imposed on them by thalassemia and use it as a positive point to reinforce their ambitions and self-confidence. Gollo et al (2013) showed that there was no difference but the findings of the present study were in contrary to it and a little predominance was observed in males.…”
Section: Discussioncontrasting
confidence: 94%
“…Other studies have also found impaired HRQOL in thalassemia in Italy [68], the UK [9], and in a small US cohort [10]. Only a single small (N=43) recent study in Italy [11] has examined change in HRQOL in thalassemia, finding improvement over 8 years, associated with a shift in the distribution of chelator choice over the same time period.…”
Section: Introductionmentioning
confidence: 99%